Reserve-building as a buffer for depression among individuals living with disability: a longitudinal study of current activities related to brain health - Schwartz, Carolyn E.; Borowiec, Katrina; Rapkin, Bruce D. (Frontiers in Psychology, 2024)
Aims This study examined whether reserve-building activities are associated with attenuated reported depression among people who were disabled from work due to a medical condition as compared to employed, retired, and unemployed participants. Methods This secondary analysis included 771 individuals, who provided data at three time points: baseline (late Spring 2020), follow-up 1 (Spring 2021), and follow-up 2 (Fall 2021). The DeltaQuest Reserve-Building Measure assessed current activities related to brain health. Analysis of variance and Pearson correlations assessed group differences on reserve-building activity scores. Classification and regression tree (CART) modeling investigated factors associated with higher and lower reported depression by employment group. Random effects (RE) models tested two buffering hypotheses: (1) comparing all groups to the employed group; (2) examining within-group effects. Results Engaging in outdoor activities, exercise, and religious/spiritual activities was associated with reduced depression over time in the overall sample. While disabled participants endorsed lower levels of active in the world, outdoors and exercise, and higher levels of inner life and passive media consumption than the other employment groups, more reserve-building activities distinguished depression levels in the disabled group’s CART models compared to the others. Among the disabled, unemployed, and retired participants, engaging in any reserve-building activities was also associated with lower depression scores, which was distinct from the employed participants. In RE models that used the employed group as the reference category, only the disabled group’s level of depression was buffered by engaging in creative activities. In within-group RE models, the disabled group’s engagement in religious/spiritual, outdoors, and games was associated with substantially reduced within-group depression, which was different from the other employment groups. In contrast, reserve-building activities were not implicated at all as buffers for employed participants. Conclusions This study revealed a beneficial effect of reserve-building activities in buffering depression over time during the COVID pandemic, particularly for disabled people. It documented that even if such individuals engaged in lesser amounts of such activities as compared to other employment groups, the buffering effect was substantial. Given the low-cost and accessible nature of reserve-building activities, it would be worthwhile to encourage such activities for disabled individuals.